International trade and inequality - Shujiro Urata; Dionisius A. Narjoko (Asian Development Bank Institute (ADBI), 2017)
The impact of globalization on equality has become a serious concern for many countries. More evidence that challenges the theoretical prediction of positive impact of international trade on income distribution has increasingly become available recently. This paper addresses this subject, surveying the empirical findings on the impact of international trade on inequalities from various perspectives. The survey reveals that an increase in trade openness by developing countries appears to have contributed to narrowing the development gap vis-à-vis developed countries, while its impacts on income gap between developing countries are not clear. The impacts of increased trade or trade liberalization on within-country inequalities are mixed. In some cases, trade liberalization improved wage-inequality, but in some other cases, the opposite pattern was observed. Similar mixed patterns are found for regional inequalities. These mixed findings are consistent with the fact that theoretical predictions are also mixed. One reason for the mixed findings is the impact of other factors affecting inequalities, including labor market conditions, inflow of capital, and policy reforms. Government needs to implement appropriate policies to deal with the inequalities. Two of the most important are policies to promote human resource development and policies on income redistribution. The former improves quality of labor, with the support from a well-functioning and flexible labor market. The latter covers policies on social safety net or on tax system. The safety net pays some portion of adjustment costs borne by workers who are adversely affected by trade liberalization, while the tax system (e.g., progressive and inheritance tax) helps distribute income more equally between the rich and the poor.
Keywords: F14; F63; O15; 330; Economics; Industry and trade